Holding health providers in developing countries accountable to consumers : a synthesis of relevant scholarship - Berlan, D. (2012)
Synthesises relevant research on health provision in low, middle and high income countries with the aim of identifying factors that shape health provider accountability to consumers, and discerning promising interventions to enhance responsiveness.